Working Times and Overweight: Tight Schedules, Weaker Fitness? - Joan Costa-Font; Belen Saenz de Miera Juarez (Institute of Labor Economics (IZA), 2018)
Although the rise in obesity and overweight is related to time constraints influencing health investments (e.g., exercise, shopping and cooking time, etc.), there is limited causal evidence to substantiate such claims. This paper estimates the causal effect of a change in working times on overweight and obesity drawing from evidence from the Aubrey reform implemented in the beginning of the past decade in France. We use longitudinal data from GAZEL (INSERM) 1997-2006 that contains detailed information about health indicators, including measures of height and weight. Taking the Alsace-Mosselle department as a control group and a difference-in-differences strategy, we estimate the effect of a differential reduction in working times on body weight. Our results show evidence of 0.7% increase in average BMI an 8pp increase in the probability of overweight among blue collars exposed to the reform. In contrast, we find no effect among white collar workers. The effects are robust to different specifications and placebo tests.
Keywords: I13; J81; 330; obesity; overweight; working times; difference-in-differences; blue collar; white collar; Body Mass Index